Risk of osteoporosis in testicular germ cell tumour survivors: A systematic review of the literature. Issue 1 (18th August 2022) - Vrouwe, Josephina P. M.; Hennus, Pauline M. L.; Hamdy, Neveen A. T.; Osanto, Susanne; Willemse, Peter‐Paul M.
Abstract: Context: Testicular germ cell tumour (TGCT) survivors are potentially at risk of developing osteoporosis, because of increased risk for disturbed bone remodelling associated with hypogonadism and anti‐cancer treatment. A number of studies show bone loss and increased fracture risk in TGCT survivors, but data are scarce. There are no clinical guidelines or recommendations issued to address skeletal health in this group of patients potentially at high risk for osteoporosis. Objective: To conduct a systematic review of available literature addressing bone health in TGCT patients. Subgroup analysis was performed to identify risk factors for bone loss and increased fracture risk. Evidence Acquisition: Relevant databases, including MEDLINE, Embase and the Cochrane Library, including all English written comparative studies addressing bone health in TGCT patients, were searched up to December 2021 and a narrative synthesis was undertaken. Risk of bias (RoB) was assessed using Cochrane ROBINS‐I tool. Evidence Synthesis: Ten studies (eight cross‐sectional and two longitudinal), recruiting a total of 1997 unique TGCT patients, were identified and included in the analysis. Bone health was reported in various ways in different studies, and subgroups were defined heterogeneously, resulting in a widely varying prevalence of osteoporosis of up to 73.2% of patients. Six studies reported low BMD associated with higher luteinizing hormone levels and one study showed a correlation between follow up duration and bone loss. Conclusions: TGCT survivors are at risk of developing osteoporosis and sustaining fragility fractures. Chemotherapy, pituitary‐gonadal axis dysfunction and ageing are key risk factors, although available data are scarce. With increasing survival of TGCT patients, a clear unmet need has been identified to systematically evaluate and monitor skeletal health in larger numbers of survivors in order to develop best clinical practice guidelines to manage the insidious but potentially preventable and treatable skeletal complications of TGCT.